Coffee, Caffeine and Cognition: A Benefit or Disadvantage? - Patočka, Jiří; Navratilova, Z.; Krejcar, O.; Kuca, K. (Bentham Science Publishers Ltd., 2019)
Coffee, one of the world's most consumed products, is extracted from the roasted seeds of Coffea sp., a plant native to Africa. The effects of coffee on the human body have been recognized for centuries and have now become the subject of systematic research. Caffeine's impact on a person's cognitive ability was reviewed through a large set of literature related to the subject. Learning and memory tasks are not typically influenced by caffeine when it comes to performance. However, in some cases, it has been used to produce inhibitory or facilitatory effects on learning and/or memory. Caffeine facilitates performance in tasks involving the working memory, but it has been seen that tasks that rely on working memory may be hindered because of it. Moreover, caffeine can augment the performance of memory during times where a person's alertness is suboptimal at best. However, a large body of research points to an improvement in reaction time. Consuming it has little to no impact on long-term memory. Caffeine can be taken as a mild stimulant, proven by its effect on performance in the context of subjects who are tired or fatigued. In some cases, it has been observed that caffeine prevents cognitive decline, specifically when it comes to healthy subjects; however, these results are heterogeneous at best. While drinking coffee positively influences both physical and mental capacity, caffeine cannot and should not be viewed as an "absolute" enhancer of cognitive function. Existing literature shows that the impact it causes on an individual is complex, and can alter, for example, anxiety, performance and arousal.
Keywords: Coffee; caffeine; pharmacology; cognition; memory; mood; vigilance; attention; alzheimer's disease; parkinson's disease